The consequences of 'in-work' benefit reform in Britain: new evidence from panel data - Marco Francesconi; Wilbert van der Klaauw (University of Essex, Institute for Social and Economic Research (ISER), 2004)
In October 1999, the British government enacted the Working Families Tax Credit, a generous tax credit aimed at encouraging work among low -income families with children. This paper uses longitudinal data collected between 1991 and 2001 to evaluate the effect of this reform on single mothers. We identify this impact by comparing changes in behavior of lone mothers to changes for single women without children. Our results show that the financial incentives of the reform had powerful effects on a wide range of lone mothers decisions. The reform led to a substantial increase in employment rates of about 7 percentage points, which was driven by both higher rates at which lone mothers remained in the labor force and higher rates at which they entered it. Womens responses were highly heterogeneous, with larger effects for mothers with one pre-school aged child, and virtually no effect for mothers with multiple older children. The reform also led to significant reductions in single mothers subsequent fertility and in the rate at which they married. Our findings suggest that the generous childcare tax credit component of the reform played a key role in explaining the estimated employment responses. Finally, we find relatively large behavioral effects in anticipation of the actual reform, which emphasizes the importance of allowing for such effects in future evaluation research.
Keywords: 330